One new genus of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from China - Yujie, Dou; Fuming, Shi (Zootaxa, 2018)
A new genus of Meconematinae is erected, i.e. Similameconema gen. nov. Nipponomeconema sinica Liu & Wang, 1998 is transferred to the new genus. The morphological characters of the species are supplemented and provided with figures. The main differences between the new genus and the genus Nipponomeconema Yamasaki, 1983 are pronotum with an entire median carina, lateral lobe slightly longer than deep; male 2nd to 5th abdominal tergites with tubular projections; the base of male cercus with a process; genitalia sclerotized. The examined specimens are deposited in the Museum of Hebei University.